Pathophysiology of the Belgrade rat - Veuthey, Tania; Wessling-Resnick, Marianne (Frontiers in Pharmacology, 2014)
The Belgrade rat is an animal model of Divalent Metal Transporter-1 (DMT1) deficiency. This strain originates from an X-irradiation experiment first reported in 1966. Since then, the Belgrade rat’s pathophysiology has helped to reveal the importance of iron balance and the role of DMT1. This review discusses our current understanding of iron transport homeostasis and summarizes molecular details of DMT1 function. We describe how studies of the Belgrade rat have revealed key roles for DMT1 in iron distribution to red blood cells as well as duodenal iron absorption. The Belgrade rat’s pathology has extended our knowledge of hepatic iron handling, pulmonary and olfactory iron transport as well as brain iron uptake and renal iron handling. For example, relationships between iron and manganese metabolism have been discerned since both are essential metals transported by DMT1. Pathophysiologic features of the Belgrade rat provide us with a unique and interesting animal model to understand iron homeostasis.